Assessing the impact of Islamic microfinancing on clients income and poverty status with reference to clients' spirituality and religiosity in Jakarta, Indonesia - Rulindo, Ronald (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2012)
This study assesses the impact of Islamic microfinancing on clients' income and poverty status with reference to the clients' spirituality and religiosity. To achieve these objectives, this study collected information from 400 micro entrepreneurs, in which 360 of them were clients of Islamic Microfinance Institutions (Islamic MFIs) in Jakarta, Indonesia. The rests of them were micro entrepreneurs who shared similar characteristics with the clients who were used as control group for comparison of the impact. This study used the Multiple and Logistic Regressions to prove the hypotheses. Overall, this study found that Islamic microfinancing, as reflected by length of having Islamic microfinancing and size of financing, is able to generate positive impact on clients' income and poverty status. However, the impact cannot be obtained in the short-term, and is only significant if the poverty status is measured by using local poverty standards; the country's formal poverty standards issued by Government Agency. The impact is relatively minimum if poverty status is measured by using international poverty standards such as extreme and moderate poverty standards, or earning US$1 and US$2 per capita per day as adopted by the World Bank and other international organizations. This study also found that the cost of financing provides no significant impact on clients' income and poverty status. Moreover, having a better economic condition is the reason why clients who obtain Mudharabah and Musharakah financing live a better life compared to those who receive Murabahah financing. Another significant finding is clients who have higher spirituality level in general are found to be wealthier than those who have lower spirituality level. Religiosity level is also found as having a significant influence on clients' income and poverty status. These findings indicate that both spirituality and religiosity should be used by the Islamic MFIs in capacity building that they provide to their clients. For this purpose, the Islamic MFIs can enhance clients' knowledge on Islamic teachings particularly in terms of aqidah, ibadah, akhlaq and muammalah, and enlighten them why these matters are not only important for the akhirah, but also for the dunya purposes, including for the improvement of their business performance. With strong aqidah and proper ibadah, they will have higher spirituality level which may enhance their passion and patience. Furthermore, with proper ibadah, good akhlaq and knowledge on muammalah, they will have higher religiosity level which may improve good characteristics that are important for their business such as discipline, hard work and human relationship management.